Anxiety and its impact on the practice of sports activities for the Police College Students - naji, Ahmed; Abdul Mohsen , Saud (Journal of Physical Education, 2011)
The research aims at : - Finding anxiety degree for the students of the college of police. - The ways of getting rid of the anxiety state that confronts the students of the college of police. The descriptive approach with a survey style has been adopted for its convenience to the nature of the research. The sample consists of (100) students of an origin (400) ,which represents a proportion (25%) of the original community. The researchers have used the anxiety meter presented by Dr. Mohammad Hassan Allawi as an instrument . The researcher have used the statistical processes represented by (the arithmetic mean, the standard deviation and T-test ). The researchers have concluded the following conclusions : 1. The presence of moral significant differences between the anxiety simple level and anxiety between the exercisers of the athletic activity and the non exercisers ,and it goes for the benefit of the exercisers. 2. The absence of statistical significant differences in hindering anxiety between the exercisers of the athletic activity and the non exercisers. 3. The psychological preparation for the exercisers of the athletic activity has been better than that of the non exercisers .